A comparative analysis of different DEM interpolation methods - Arun, Pattathal Vijayakumar (Geodesy and Cartography, 2013)
Visualization of geospatial entities generally entails Digital Elevation models (DEMs) that are interpolated to establish three dimensional co-ordinates for entire terrain. The accuracy of generated terrain model depends on the interpolation mechanism adopted and hence it is needed to investigate the comparative performance of different approaches in this context. General interpolation techniques namely Inverse Distance Weighted, Kriging, Topo to Raster, Natural Neighbor, and Spline approaches have been compared. Differential ground field survey has been conducted to generate reference DEM as well as specific set of test points for comparative evaluation. We have also investigated the suitability SRTM DEM for Indian terrain by comparing it with the SOI DEM. Contours were generated at different intervals for comparative analysis and found SRTM as more suitable. The terrain sensitivity of various methods has also been analyzed with reference to the study area.